An austenitic heat-resistant alloy, a method for manufacturing the same, and a bar
Patent Information
- Application Number
- CN202611108635.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]鉴于上述分析,本发明实施例旨在提供一种奥氏体耐热合金及其制备方法,用以至少解决现有低镍铁镍基合金持久性能不足、硬度过低的问题之一
1)本发明通过控制Ti/Al比在0.80~1.20,并添加0.005~0.050%的Zr和0.005~0.030%的Ce,使合金组织为γ+γ’+M23C6,晶界处均匀分布含Zr和Ce的弥散相,抑制了有害η相的析出,获得了纯净的合金组织,固溶态硬度为HRC19~21。将上述合金通过本发明的制备方法制成棒材时,纯净的合金组织保证了冷拔变形的均匀性,配合15~19%的冷拔变形量,使棒材达到高温持久性能(700℃/250MPa下持久寿命达400h以上,700℃/350MPa下持久寿命达220h以上)和高硬度(HRC25~HRC35)的协同提升。
Smart Images

Figure CN122879602A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of special alloy technology, and in particular to an austenitic heat-resistant alloy, its preparation method, and its bar stock. Background Technology
[0002] Heat-resistant alloys are alloys that exhibit excellent oxidation resistance, creep resistance, and durability at high temperatures. They are widely used in high-temperature components of advanced equipment such as aero engines, gas turbines, and nuclear reactors. Iron-based heat-resistant alloys hold an important position among heat-resistant alloys due to their significant cost advantages, and their operating temperature range is typically 600–800℃.
[0003] Existing iron-based heat-resistant alloys are mainly divided into two categories: solid solution strengthened and precipitation strengthened. Precipitation strengthened alloys typically add elements such as Al and Ti to form a γ' phase (Ni3(Al,Ti)) as the main strengthening phase, and add Cr to ensure oxidation resistance, while adding elements such as Nb and V helps strengthen the alloy. This type of alloy has a certain high-temperature strength in the temperature range of 650~750℃ and has been used to manufacture high-temperature components such as engine valves and turbine blades.
[0004] However, existing precipitation-strengthened iron-based heat-resistant alloys still have some technical problems. For example, they have insufficient creep resistance, with creep life generally less than 200 hours under high stress conditions of 700℃ / 350MPa, making it difficult to meet the requirements of components with higher loads; their hardness is low, with hardness usually below HRC20 when delivered in the solution state, resulting in poor wear resistance and resistance to surface damage; and their microstructure stability is poor, with harmful η phase easily precipitating during long-term service or hot working, leading to accelerated performance degradation. Summary of the Invention
[0005] Based on the above analysis, the present invention aims to provide an austenitic heat-resistant alloy and its preparation method, so as to at least solve one of the problems of insufficient creep performance and excessively low hardness of existing low-nickel iron nickel-based alloys.
[0006] On one hand, embodiments of the present invention provide an austenitic heat-resistant alloy with the following chemical composition by mass percentage: C: 0.03~0.15%, Si: ≤0.5%, Mn: ≤1.0%, P: ≤0.020%, S: ≤0.020%, Cr: 16.0~22.0%, Ni: 24.0~29.0%, Al: 0.50~2.50%, Ti: 1.00~2.20%, Nb: 0.50~2.00%, V: 0.10~0.50%, Mo: 0.30~2.00%, Zr: 0.005~0.050%, Ce: 0.005~0.030%, with the remainder being Fe and unavoidable impurities, wherein Ti / Al = 0.80~1.20.
[0007] Furthermore, by mass percentage, Ti / Al = 0.90~1.10 and Mo = 0.50~1.50%.
[0008] To enable the industrial production of the alloy, this invention also provides a method for preparing the above-mentioned austenitic heat-resistant alloy, comprising the following steps: S1: Vacuum induction melting is carried out. In the later stage of refining, Zr and Ce are added in the form of Si-Zr alloy and Si-Ce alloy respectively. Then, electroslag remelting is carried out to obtain electroslag ingots. S2: Forging the electroslag ingot into a square billet; S3: The billet is hot rolled into a bar, and immediately after rolling, it is cooled by water, followed by water cooling. S4: Cool after solution treatment; S5: The solution-treated bar is cold-drawn and deformed, with a total deformation of 15-19%.
[0009] Furthermore, in S1, Si-Zr alloy is added when the molten steel temperature is 1420~1450℃, and Si-Ce alloy is added when the molten steel temperature is 1430~1460℃.
[0010] Furthermore, when adding Si-Zr alloy and Si-Ce alloy, after controlling the vacuum degree of the vacuum chamber to <1Pa, high-purity argon gas is introduced to raise the pressure inside the furnace to 6000~8000Pa, so as to suppress the volatilization of Zr and Ce elements.
[0011] Furthermore, in S2, the forging opening temperature is 1130~1150℃, and the final forging temperature is 920~940℃.
[0012] Furthermore, in S3, the hot rolling temperature is 1100~1120℃, and the final rolling temperature is 910~930℃.
[0013] Furthermore, in S3, the coolant used for water cooling is composed of water, sodium dodecyl sulfate, nano copper oxide powder, and nano aluminum oxide powder, wherein the amount of sodium dodecyl sulfate added is 0.20~0.50wt%, and the amount of nano copper oxide powder and nano aluminum oxide powder added is 0.1~0.3wt%.
[0014] Furthermore, in S5, the cold drawing process involves 2 to 3 consecutive cold drawing deformations.
[0015] Furthermore, the present invention also provides a heat-resistant alloy rod, which is made of the above-mentioned austenitic heat-resistant alloy, and the hardness of the heat-resistant alloy rod is HRC25~HRC35.
[0016] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects: 1) This invention controls the Ti / Al ratio to be between 0.80 and 1.20, and adds 0.005% to 0.050% Zr and 0.005% to 0.030% Ce to achieve an alloy microstructure of γ+γ'+M. 23 C6, with uniformly distributed Zr and Ce-containing dispersed phases at grain boundaries, suppresses the precipitation of harmful η phase, resulting in a pure alloy microstructure with a solution hardness of HRC19~21. When the above alloy is made into bars using the preparation method of this invention, the pure alloy microstructure ensures the uniformity of cold drawing deformation. Combined with a cold drawing deformation amount of 15~19%, the bars achieve a synergistic improvement in high-temperature creep performance (creep life of over 400h at 700℃ / 250MPa, and over 220h at 700℃ / 350MPa) and high hardness (HRC25~HRC35).
[0017] 2) This invention improves the high-temperature creep resistance of the alloy by adding 0.30~2.00% Mo and controlling the Ti / Al ratio within the range of 0.80~1.20, utilizing the synergistic effect of Mo's solid solution strengthening and γ' phase strengthening. The alloy's creep life is significantly improved compared to traditional Ni30 alloys.
[0018] 3) In the prior art, austenitic heat-resistant alloys are usually supplied directly in the solution state after solution treatment. The alloy hardness is lower than HRC20, and the wear resistance and surface damage resistance are insufficient. The present invention adds a cold drawing deformation process after solution treatment. The total deformation is controlled at 15~19%. No intermediate annealing is performed between cold drawing and cold drawing. The hardness of the bar is greatly increased to HRC25~35 by utilizing cold drawing work hardening, which significantly improves the wear resistance and surface damage resistance of the bar.
[0019] 4) This invention employs Si-Zr and Si-Ce master alloys, added in stages during the later stages of vacuum induction melting and refining, coupled with controlled protective atmosphere, ensuring high yields of Zr and Ce. Existing cold drawing processes for austenitic heat-resistant alloys typically require intermediate annealing between passes. However, this invention achieves the required hardness in bars through 2-3 consecutive cold drawing passes with a total deformation of 15-19%, eliminating the need for intermediate annealing. This shortens the production cycle and reduces energy consumption and manufacturing costs.
[0020] 5) In the water cooling step after hot rolling, this invention uses a coolant composed of water, sodium dodecyl sulfate, nano-copper oxide, and alumina powder. Sodium dodecyl sulfate acts as a dispersant, while copper oxide and alumina synergistically improve the thermal diffusivity of the coolant. Compared with pure water cooling, the coolant of this invention can achieve a faster cooling rate and suppress internal cracking caused by excessive internal temperature rise in the alloy.
[0021] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0022] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0023] Figure 1 This is a schematic diagram of the water cooling device of the present invention; Figure 2 Metallographic diagram of the η phase in Ni30 alloy; Figure 3 Metallographic diagram of the η phase in alloy of Comparative Example 1; Figure 4 Metallographic diagram of Ni30 alloy after rolling; Figure 5 The image shows the metallographic structure of the alloy in Example 1 after solution treatment and 16.5% cold drawing.
[0024] Figure label: 1. Workpiece; 2. First frame; 3. Water tank; 4. Water pump; 5. Pipe; 6. Water flow switch; 7. Nozzle; 8. Second frame. Detailed Implementation
[0025] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0026] Existing austenitic heat-resistant alloys generally suffer from insufficient durability and low hardness. To address these issues, this invention proposes an austenitic heat-resistant alloy and its preparation method.
[0027] In one specific embodiment of the present invention, an austenitic heat-resistant alloy is disclosed, the chemical composition of which, by mass percentage, is: C: 0.03~0.15%, Si: ≤0.5%, Mn: ≤1.0%, P: ≤0.020%, S: ≤0.020%, Cr: 16.0~22.0%, Ni: 24.0~29.0%, Al: 0.50~2.50%, Ti: 1.00~2.20%, Nb: 0.50~2.00%, V: 0.10~0.50%, Mo: 0.30~2.00%, Zr: 0.005~0.050%, Ce: 0.005~0.030%, with the remainder being Fe and unavoidable impurities, wherein Ti / Al = 0.80~1.20.
[0028] The functions and roles of each element in the above alloy composition are as follows: Titanium (Ti) and aluminum (Al): Ti and Al combine with Ni to form the γ' phase (Ni3(Al,Ti)), which is the most important strengthening phase in austenitic heat-resistant alloys. Its quantity, size, distribution, and stability directly determine the high-temperature mechanical properties of the alloy. When the Ti / Al ratio is too high, excess Ti promotes the precipitation of the harmful η phase (Ni3Ti). The η phase consumes Ti, reducing the strengthening effect of the γ' phase and damaging the plasticity and toughness of the alloy. When the Ti / Al ratio is too low, the β phase (NiAl) easily precipitates at the grain boundaries. This phase is hard and brittle, reducing the toughness of the alloy. This invention controls the Ti / Al ratio within the range of 0.80~1.20 (e.g., 0.80, 0.85, 0.90, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20), ensuring that the γ' phase has an appropriate Ti / Al ratio, achieving sufficient precipitation strengthening effect while avoiding the formation of the η phase.
[0029] Molybdenum (Mo) is an important solid solution strengthening element. Mo atoms have a large atomic radius, and when dissolved into the matrix, they cause lattice distortion, hindering dislocation movement and thus increasing the alloy's strength. This effect is particularly pronounced at high temperatures. More importantly, Mo exhibits a synergistic strengthening effect with the γ' phase: after dissolving into the matrix, Mo reduces the mismatch between the γ' phase and the matrix, decreasing interfacial energy and making the γ' phase more stable and less prone to coarsening at high temperatures. This invention controls the Mo content within a low Mo range of 0.30–2.00% (e.g., 0.30%, 0.50%, 0.80%, 1.00%, 1.20%, 1.50%, 1.80%, 2.00%), and combines it with a Ti / Al ratio of 0.80–1.20, allowing the solid solution strengthening of Mo and the precipitation strengthening of the γ' phase to mutually promote each other, jointly improving the alloy's high-temperature creep resistance.
[0030] Preferably, the best synergistic strengthening effect can be obtained by using Mo at a concentration of 0.50~1.50% and in combination with Ti / Al = 0.90~1.10.
[0031] Zirconium (Zr) and cerium (Ce) are key trace elements for grain boundary regulation. During the high-temperature service of alloys, harmful phases (such as η phase and σ phase) preferentially precipitate at grain boundaries, and cracks easily initiate and propagate along these boundaries. This invention combines Zr and Ce, with Zr added at a concentration of 0.005~0.050%, for example, 0.005%, 0.010%, 0.015%, 0.020%, 0.025%, 0.030%, 0.040%, and 0.050%; and Ce added at a concentration of 0.005~0.030%, for example, 0.005%, 0.010%, 0.015%, 0.020%, 0.025%, and 0.030%. By utilizing the segregation behavior of these two elements at grain boundaries, a dispersed phase containing Zr and Ce is formed, anchoring it at the grain boundaries and suppressing the precipitation of the harmful η phase. Furthermore, it hinders grain boundary migration and grain coarsening, thereby improving the high-temperature creep strength of the alloy. In addition, there is a synergistic effect between the two elements: Zr preferentially combines with C to form carbides, while Ce tends to combine with O and S to form oxides or sulfides, which together cover the grain boundary surface and form a more complete grain boundary pinning layer.
[0032] Nickel (Ni): Ni, together with Fe, constitutes the austenitic matrix, providing the alloy's basic plasticity and toughness. This invention controls the Ni content to 24.0~29.0% (e.g., 24.0%, 25.0%, 26.0%, 27.0%, 28.0%, 29.0%), ensuring good austenitic stability in the matrix and preventing martensitic transformation during processing or service. Simultaneously, Ni is the main component of the γ' phase, combining with Al and Ti to form the Ni3(Al,Ti) reinforcing phase; sufficient Ni content is a prerequisite for ensuring the complete precipitation of the γ' phase. In existing technologies, the Ni content of nickel-based alloys is typically above 30%. This invention employs an iron-nickel-based design (Ni content 24~29%), reducing alloy costs while ensuring high-temperature performance.
[0033] Chromium (Cr): Chromium is the main element providing the alloy with antioxidant and corrosion-resistant properties. In this invention, the Cr content is controlled at 16.0% to 22.0%, for example, 16.0%, 17.0%, 18.0%, 19.0%, 20.0%, 21.0%, and 22.0%. Cr forms a dense Cr₂O₃ oxide film on the alloy surface, preventing oxygen from diffusing into the alloy interior, thereby improving the alloy's high-temperature oxidation resistance.
[0034] Carbon (C): Carbon is a carbide-forming element in alloys. In this invention, the C content is controlled at 0.03~0.15%, for example, 0.03%, 0.05%, 0.08%, 0.10%, 0.12%, and 0.15%. Appropriate amounts of C form carbides (such as Mn) with elements like Cr, Nb, and Zr. 23 Carbides such as C6, NbC, and ZrC are distributed on grain boundaries, which pin the grain boundaries and inhibit grain coarsening.
[0035] Niobium (Nb): Niobium is a supplementary strengthening element that effectively pins dislocations and grain boundaries by forming stable carbonitride precipitates, thereby improving the high-temperature strength of the alloy. In this invention, the Nb content is controlled at 0.50~2.00%, for example, 0.50%, 0.80%, 1.00%, 1.20%, 1.50%, 1.80%, and 2.00%.
[0036] Vanadium (V): Vanadium is a microalloying element. V combines with carbon to form VC-type carbides, which have a high precipitation temperature and can inhibit grain growth during hot working. In this invention, the V content is controlled at 0.10~0.50%, for example, 0.10%, 0.20%, 0.30%, 0.40%, and 0.50%. The addition of V also helps improve the wear resistance of the alloy, and, in conjunction with the hardness formed by subsequent cold drawing work hardening, further improves the surface damage resistance of the bar stock.
[0037] Silicon (Si): Silicon is a deoxidizing element and a residual element. During smelting, Si has excellent deoxidizing ability, removing oxygen from molten steel and improving alloy purity. However, excessive Si content promotes the precipitation of harmful phases such as the σ phase, reducing the alloy's plasticity and toughness. Therefore, this invention controls Si content to ≤0.5%. It should be noted that Zr and Ce are added in the form of Si-Zr alloys and Si-Ce alloys in this invention. Trace amounts of Si will inevitably be introduced into the intermediate alloy, but by controlling the amount added to the intermediate alloy, the Si content in the final alloy can be ensured not to exceed the above-mentioned range.
[0038] Manganese (Mn): Manganese is a deoxidizing and desulfurizing element. Mn combines with sulfur to form MnS, reducing the harmful effects of sulfur. This invention controls the Mn content to ≤1.0%. Excessive Mn content will reduce the alloy's oxidation resistance and easily form harmful non-metallic inclusions.
[0039] Phosphorus (P) and sulfur (S) are harmful impurity elements. P and S segregate at grain boundaries, reducing grain boundary bonding strength and easily leading to cracking during hot working and brittle fracture during service. This invention controls P to ≤0.020% and S to ≤0.020%.
[0040] Iron (Fe): Iron is the matrix element of the alloy. Apart from the elements mentioned above and unavoidable impurities, the rest is Fe. The addition of Fe reduces the cost of the alloy and, together with Ni, forms a stable austenitic matrix.
[0041] In summary, the austenitic heat-resistant alloy provided in this embodiment optimizes the strengthening effect of the γ' phase by controlling the Ti / Al ratio, utilizes the synergistic effect of Mo's solid solution strengthening and γ' phase strengthening, and simultaneously adds trace amounts of Zr and Ce to form dispersed phases at grain boundaries to pin the grain boundaries and suppress the precipitation of harmful η phase. The strengthening effects of elements such as Cr, Nb, and V further enhance the alloy's microstructure, resulting in a γ+γ'+M microstructure. 23 C6 alloys exhibit uniformly distributed Zr and Ce-containing dispersed phases at grain boundaries, with a solid solution hardness of HRC 19-21. This enhances the alloy's high-temperature stability, creep resistance, and overall mechanical properties, resulting in a significantly longer creep life compared to traditional Ni30 alloys. When the alloy is formed into bars, a 15-19% cold-drawing deformation can further increase the bar hardness to HRC 25-35.
[0042] A method for preparing the above-mentioned austenitic heat-resistant alloy includes the following steps: S1: Vacuum induction melting is carried out. In the later stage of refining, Zr and Ce are added in the form of Si-Zr alloy and Si-Ce alloy respectively. Then, electroslag remelting is carried out to obtain electroslag ingots. S2: Forging the electroslag ingot into a square billet; S3: The billet is hot rolled into a bar, and immediately after rolling, it is cooled by water, followed by water cooling. S4: Cool after solution treatment; S5: The solution-treated bar is cold-drawn and deformed, with a total deformation of 15-19%.
[0043] Specifically, in S1, vacuum induction melting is used for the first stage of smelting, followed by electroslag remelting. It should be noted that medium-frequency induction furnace smelting or electric furnace smelting can also be used instead of vacuum induction melting. Strict control of the raw material composition is necessary during the smelting process to ensure the purity of the alloy.
[0044] Because Al, Ti, Zr, and Ce are easily burned and oxidized, these elements are added in the later stages of refining. Zr and Ce are added in the form of Si-Zr alloy and Si-Ce alloy, respectively. This is because pure Zr and pure Ce are extremely chemically reactive. Adding them as intermediate alloys can reduce the activity of the alloying elements, increase the melting point, reduce volatilization, and make them more soluble in molten steel.
[0045] In the later stages of refining, the vacuum level in the vacuum chamber is first controlled to be <1 Pa to remove residual air. Then, high-purity argon is introduced to raise the furnace pressure to 6000~8000 Pa, for example, 6000 Pa, 6200 Pa, 6500 Pa, 6800 Pa, 7000 Pa, 7300 Pa, 7500 Pa, 7800 Pa, or 8000 Pa, thereby suppressing the volatilization of Zr and Ce. Under the condition of maintaining this protective atmosphere, the temperature of the molten steel is first controlled at 1420~1450℃, for example, 1420℃, 1425℃, 1430℃, 1435℃, 1440℃, 1445℃, or 1450℃. After the temperature stabilizes, the valve between the special hopper and the vacuum chamber is opened, and the Si-Zr alloy block falls into the high-temperature molten steel pool by gravity, completing the Si-Zr alloy feeding operation. This step requires precise control of the molten steel temperature between 1420 and 1450°C. If the temperature is too low, the Si-Zr alloy will not melt sufficiently, and the Zr element will not be evenly distributed. If the temperature is too high, the volatilization loss of Zr will increase dramatically.
[0046] Subsequently, while maintaining the protective atmosphere, the temperature of the molten steel is further adjusted to 1430~1460℃, for example, 1430℃, 1435℃, 1440℃, 1445℃, 1450℃, 1455℃, and 1460℃. After the temperature stabilizes, the valve between the special hopper and the vacuum chamber is opened, and the Si-Ce alloy block falls into the high-temperature molten steel pool by gravity, completing the Si-Ce alloy feeding operation. This temperature window needs to be slightly higher than the Si-Zr alloy feeding temperature, as Ce requires a higher degree of superheating to fully melt. If the temperature is too low, the Si-Ce alloy will not melt sufficiently, and the Ce element distribution will be uneven; if the temperature is too high, the volatilization loss of Ce will increase significantly.
[0047] This invention employs the method of adding the above-mentioned Si-Zr and Si-Ce master alloys in stages during the later stages of refining, combined with protective atmosphere control, which effectively suppresses the volatilization of Zr and Ce, ensuring the high-efficiency yield of these two key elements, and enabling the formation of a sufficient number of Zr and Ce-containing dispersed phases at the grain boundaries, thereby fully exerting the role of pinning grain boundaries and suppressing the precipitation of harmful η phase.
[0048] After the aforementioned alloying elements are added, the molten steel temperature is adjusted to a pouring temperature of 1430℃~1490℃ for pouring. After pouring, it is allowed to cool statically for 3~4 hours to obtain a vacuum induction ingot. This vacuum induction ingot is then used as a consumable electrode for electroslag remelting to further remove non-metallic inclusions in the molten steel, improving the purity of the alloy and the uniformity of the as-cast microstructure. After electroslag remelting, the ingot needs to undergo annealing to eliminate internal stress and homogenize the microstructure. The annealed ingot is first trimmed at the head and tail to remove the parts with more impurities at the head and tail, and then the surface is polished to clean surface defects, obtaining a smooth electroslag ingot, preparing it for subsequent forging.
[0049] Specifically, in S2, the cleaned electroslag ingot is forged into a billet on a 2000-ton high-speed forging mill at a forging temperature of 1130~1150℃ (e.g., 1130℃, 1135℃, 1140℃, 1145℃, 1150℃) and a final forging temperature of 920~940℃ (e.g., 920℃, 925℃, 930℃, 935℃, 940℃), forging it into a square billet for subsequent hot rolling. In existing technologies, the final forging temperature is typically controlled above 950℃, which, while beneficial for reducing deformation resistance, easily leads to grain coarsening. This invention appropriately lowers the final forging temperature to 920~940℃, achieving a finer forged microstructure while ensuring smooth forging, thus providing a square billet with a uniform microstructure for subsequent hot rolling.
[0050] Specifically, in S3, the aforementioned billet is hot-rolled into bars at a temperature of 1100~1120℃ and a final rolling temperature of 910~930℃. Water cooling is used during the rolling process to control the internal temperature rise of the alloy.
[0051] like Figure 1 As shown, the water-cooled device consists of a water tank 3, a water pump 4, a conduit 5, a water flow switch 6, and a nozzle 7. The workpiece 1 (i.e., the hot-rolled bar) passes through the first frame 2 and the second frame 8 in sequence. The water pump 4 draws coolant from the water tank 3 and delivers it to the nozzle 7 through the conduit 5. The water flow switch 6 is used to adjust the flow rate and pressure. The nozzle 7 sprays the coolant onto the surface of the workpiece 1 for rapid cooling.
[0052] Furthermore, the coolant used in the water cooling system is composed of water, sodium dodecyl sulfate, nano copper oxide powder, and nano aluminum oxide powder.
[0053] Sodium dodecyl sulfate is used as a dispersant, with an addition amount of 0.20~0.50wt%, to prevent the aggregation of nanoparticles. If the addition amount is less than 0.20wt%, the dispersion effect is insufficient, and the nanoparticles are prone to agglomeration and precipitation. If the addition amount is greater than 0.50wt%, too much foam will be generated, affecting the fluidity and cooling uniformity of the coolant.
[0054] The addition amounts of both nano-copper oxide powder and nano-alumina powder were 0.1–0.3 wt%, with particle sizes of 30–80 nm and a purity of 99.9%. Too low an addition amount resulted in minimal thermal conductivity enhancement, while too high an addition amount led to excessively high coolant viscosity and poor flowability. Copper oxide and alumina nanoparticles differ in thermal conductivity and morphology; their combination in the base fluid forms a denser thermally conductive network, producing a synergistic enhancement effect and improving the thermal diffusivity of the coolant.
[0055] Due to the synergistic effect of the aforementioned nanoparticles, the thermal diffusivity of this coolant is higher than that of pure water, enabling a faster cooling rate than pure water. This effectively suppresses internal cracking of the material caused by excessive internal temperature rise during rolling. After rolling, it is further cooled to room temperature by water cooling.
[0056] Specifically, in S4, a solution treatment is performed to fully dissolve the reinforcing phases, such as the γ' phase, into the matrix. The mixture is then cooled to room temperature to prepare for subsequent cold drawing deformation. The purpose of the solution treatment is to eliminate non-equilibrium structures that may occur during hot rolling and cooling, obtaining a uniformly composed supersaturated solid solution, thereby ensuring the stability and consistency of the subsequent cold drawing work hardening effect.
[0057] Specifically, in S5, to improve the hardness of the material, this invention performs cold drawing on the solution-treated bar. After conventional solution treatment, the alloy hardness is usually below HRC20, which cannot meet the hardness requirements of subsequent blanking (generally, it needs to be controlled between HRC25 and 35: too low hardness can easily lead to material adhesion and increase waste; too high hardness makes blanking difficult and reduces efficiency). Therefore, this invention adds a cold drawing deformation process after solution treatment, using work hardening to increase the bar hardness from below HRC20 to HRC25-35.
[0058] Furthermore, the total cold drawing deformation is controlled within 15-19%, for example, 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, and 19%. Two to three consecutive cold drawing deformations are performed without intermediate annealing or grinding between passes. After cold drawing, a polishing process is carried out to obtain the final heat-resistant alloy bar.
[0059] If the cold drawing deformation exceeds 20%, and intermediate annealing or grinding is performed between passes, the material surface will crack due to excessively rapid work hardening. This invention employs a lower total deformation of 15-19%. On the one hand, this deformation is sufficient to produce adequate work hardening; on the other hand, the lower deformation ensures a moderate accumulation of work hardening between passes, allowing for continuous completion of all cold drawing deformation without intermediate annealing, while maintaining a good surface condition that eliminates the need for grinding.
[0060] The bars processed by the above process not only meet the hardness requirements of subsequent blanking and processing, significantly improving the wear resistance and surface damage resistance of the bars, but also avoid the sticking problem caused by low hardness or the blanking difficulty caused by excessive hardness.
[0061] The present invention will be described in more detail below through specific embodiments. These embodiments are merely descriptions of the best implementation of the invention and do not limit the scope of the invention in any way.
[0062] Examples 1-5 Austenitic heat-resistant alloy bars were prepared using the following method according to the chemical compositions shown in Examples 1-5 of Table 1: S1: Vacuum induction melting and electroslag remelting. Vacuum induction melting is used for the first stage of smelting. Al and Ti are added in the later stages of refining, while Zr and Ce are added in the later stages of refining as Si-Zr and Si-Ce alloys, respectively. When adding the Si-Zr alloy, the molten steel temperature is controlled at 1420~1450℃; when adding the Si-Ce alloy, the temperature is controlled at 1430~1460℃. During the addition process, the vacuum level in the vacuum chamber is initially controlled to <1Pa, followed by the introduction of high-purity argon gas to raise the furnace pressure to 6000~8000Pa. After the alloying elements are added, the molten steel temperature is adjusted to the pouring temperature of 1430℃~1490℃ for pouring. After pouring, the ingot is allowed to cool statically for 3~4 hours to obtain a vacuum induction ingot. The vacuum induction casting ingot was used as a consumable electrode for electroslag remelting. After electroslag remelting, the ingot was annealed, then the head and tail were cut off, and the surface was polished to obtain a smooth electroslag ingot.
[0063] S2: Forging and billet preparation. The cleaned electroslag ingot is forged and billet prepared on a 2000-ton high-speed forging mill. The forging and billet preparation temperature is 1130~1150℃, and the final forging temperature is 920~940℃, forging it into a square billet.
[0064] S3: Hot rolling and water cooling. The above-mentioned billets are hot rolled into bars at a temperature of 1100~1120℃ and a finishing rolling temperature of 910~930℃. Water cooling is used during the rolling process, and a cooling liquid is sprayed for cooling during the finishing rolling stage. This cooling liquid is composed of water, sodium dodecyl sulfate, nano copper oxide powder, and nano alumina powder, wherein the amount of sodium dodecyl sulfate added is 0.20~0.50wt%, and the amount of nano copper oxide powder and nano alumina powder added is 0.1~0.3wt% each. After rolling, the bars are cooled to room temperature by water cooling.
[0065] S4: Solution treatment: After holding at 1000℃ for 30 minutes, water cooling treatment is performed.
[0066] S5: Cold drawing deformation and polishing. The solution-treated bar is cold-drawn, with the total deformation controlled at 15-19%. Two to three consecutive cold-drawing passes are used, with the deformation evenly distributed across each pass. No intermediate annealing is performed between passes. After cold drawing, the bar is polished to obtain the final heat-resistant alloy bar.
[0067] The chemical composition of Examples 1-5 is shown in Table 1, the specific process parameters are shown in Table 2, and the performance test results are shown in Table 3.
[0068] Comparative Examples 1-2 The chemical compositions of Comparative Examples 1 and 2 are shown in Table 1, respectively. Compared with Examples 1-5, the Ti / Al ratio of Comparative Example 1 is 1.96 (exceeding the upper limit of 1.20 of this invention), and the Ti / Al ratio of Comparative Example 2 is 0.62 (below the lower limit of 0.80 of this invention). Apart from this, the contents of other alloying elements in Comparative Examples 1-2 are all within the range of this invention, and their preparation methods are exactly the same as those in Example 1 (including steps S1-S5 and corresponding process parameters). The specific process parameters of Comparative Examples 1-2 are shown in Table 2, and the performance test results are shown in Table 3.
[0069] Comparative Examples 3-4 The chemical compositions of Comparative Examples 3 and 4 are shown in Table 1. Compared with Examples 1-5, the alloys of Comparative Examples 3 and 4 do not contain Zr and Ce (the contents of other elements are all within the range of this invention, and the Ti / Al ratios are 0.96 and 0.83, respectively, both within the range of 0.80~1.20). In the preparation process, the main process of Comparative Examples 3-4 is consistent with that of Example 1, except that the special feeding operation of adding Si-Zr alloy and Si-Ce alloy in step S1 is omitted. The other process steps (including S2-S5) are exactly the same as those of Example 1. The specific process parameters of Comparative Examples 3-4 are shown in Table 2, and the performance test results are shown in Table 3.
[0070] Table 1 Chemical composition (wt%) of the examples and comparative examples
[0071] Table 2 Forging and Rolling Process Parameters
[0072] Note: The coolant mixing ratio number corresponds to Table 5.
[0073] Table 3. Alloy microstructure and creep properties of the examples and comparative examples
[0074] As shown in Table 3, the tissues in Examples 1-5 were all γ+γ'+M. 23 C6, no harmful phases (see...) Figure 5 (Representative figure of Example 1), its creep rupture lifetime under 700℃ / 250MPa conditions reached 401h54'~425h42'. As a control, a small amount of η phase (e.g., ...) appeared in the microstructure of Ni30 in the rolled state and Comparative Example 1. Figure 2 and Figure 3As shown in the figures, the durability of Comparative Examples 1-5 was 321h59' and 318h42', respectively; a small amount of β phase appeared in the tissue of Comparative Example 2, and the durability was only 333h12'. The durability of Comparative Examples 3-4 was only 305h42' and 311h18', respectively, which was significantly lower than that of Examples 1-5.
[0075] Comparative Example 5 Based on Example 1, only the final forging temperature was reduced to 905°C. All other chemical compositions and process parameters (including the forging temperatures in S1, S3, S4, S5 and S2) were exactly the same as in Example 1, serving as Comparative Example 5.
[0076] Comparative Example 6 Based on Example 2, only the final rolling temperature was reduced to 902°C, while the remaining chemical composition and all process parameters (including the initial rolling temperature in S1, S2, S4, S5 and S3) were exactly the same as in Example 2, serving as Comparative Example 6.
[0077] The specific process parameters for comparative examples 5-6 are shown in Table 2.
[0078] As shown in Table 2, Comparative Examples 5 and 6 both exhibited surface cracking after forging or rolling, while Examples 1 and 2 showed normal surface conditions.
[0079] Comparative Example 7 Based on Example 1, only the total cold drawing deformation was reduced to 12.5%, while the remaining chemical composition and all process parameters (including steps S1-S4 and the number of cold drawing passes in S5) were exactly the same as in Example 1, serving as Comparative Example 7.
[0080] Comparative Example 8 Based on Example 1, only the total cold drawing deformation was increased to 25.0%, while the remaining chemical composition and all process parameters were exactly the same as in Example 1, serving as Comparative Example 8.
[0081] Comparative Example 9 Based on Example 2, only the total cold drawing deformation was reduced to 11.5%, while the remaining chemical composition and all process parameters (including steps S1-S4 and the number of cold drawing passes in S5) were exactly the same as in Example 2, serving as Comparative Example 9.
[0082] Comparative Example 10 Based on Example 2, only the total cold drawing deformation was increased to 21.2%, while the remaining chemical composition and all process parameters were exactly the same as in Example 2, serving as Comparative Example 10.
[0083] The cold drawing deformation, hardness, and microstructure of each embodiment and comparative examples 7-10 are shown in Table 4.
[0084] Table 4 Cold drawing deformation and hardness
[0085] As shown in Table 4, when the cold drawing deformation of Examples 1-5 is 15-19%, the alloy hardness is HRC 27.8-32.4, and the microstructure is normal (see Table 4). Figure 5 (Representative figure of Example 1). The cold drawing deformation amounts of Comparative Examples 7 and 9 were 12.5% and 11.5% respectively (both less than 15%), and their hardnesses were HRC22.4 and HRC23.2 respectively (both less than HRC25), which did not meet the hardness requirements of this invention. The cold drawing deformation amounts of Comparative Examples 8 and 10 were 25.0% and 21.2% respectively (both more than 20%), and although their hardnesses reached HRC34.2 and HRC33.6, deformation bands appeared in the microstructure.
[0086] Furthermore, based on the complete preparation process of Example 1, only the proportions of each component in the coolant in step S3 were changed; all other chemical compositions and process parameters remained identical to those in Example 1. The proportions of each coolant and the test results of its thermal conductivity are shown in Table 5.
[0087] Table 5 Coolant proportions and thermal conductivity
[0088] When the amount of sodium dodecyl sulfate added is 0.20~0.50wt%, and the amount of nano copper oxide and nano aluminum oxide added is 0.1~0.3wt% (corresponding to ratios 1~6 in Table 5), the thermal conductivity of the coolant is 0.643~0.712W / m·K, which is significantly higher than that of pure water (0.606W / m·K), enabling a faster cooling rate and resulting in rods with good surface quality.
[0089] When the amount of nano-alumina added is less than 0.1 wt% (e.g., 0.08 wt%), or the amount of nano-copper oxide added is less than 0.1 wt% (e.g., 0.08 wt%), or the amount of sodium dodecyl sulfate added is less than 0.20 wt% (e.g., 0.10 wt%) (corresponding to ratios 7-10 in Table 5), the thermal conductivity of the coolant is only 0.588-0.612 W / m·K, which is close to or even lower than that of pure water, failing to achieve the expected cooling effect, and resulting in a decrease in the surface quality of the rod. The above results indicate that controlling the sodium dodecyl sulfate content in the coolant at 0.20-0.50 wt%, and controlling both nano-copper oxide and nano-alumina at 0.1-0.3 wt%, is the preferred ratio for obtaining good cooling performance.
[0090] In summary, this invention effectively suppresses the precipitation of harmful phases and significantly improves the durability of the alloy by rationally matching the Ti / Al ratio and adding Zr and Ce in an austenitic heat-resistant alloy, combined with optimized hot working and cold drawing deformation processes. At the same time, it achieves suitable hardness and intact microstructure, successfully realizing the synergistic effect of alloy composition and preparation process.
[0091] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. An austenitic heat-resistant alloy, characterized in that, The chemical composition by mass percentage is as follows: C: 0.03~0.15%, Si: ≤0.5%, Mn: ≤1.0%, P: ≤0.020%, S: ≤0.020%, Cr: 16.0~22.0%, Ni: 24.0~29.0%, Al: 0.50~2.50%, Ti: 1.00~2.20%, Nb: 0.50~2.00%, V: 0.10~0.50%, Mo: 0.30~2.00%, Zr: 0.005~0.050%, Ce: 0.005~0.030%, with the remainder being Fe and unavoidable impurities. The Ti / Al ratio is 0.80~1.
20.
2. The austenitic heat-resistant alloy according to claim 1, characterized in that, By mass percentage, Ti / Al = 0.90~1.10 and Mo = 0.50~1.50%.
3. A method for preparing austenitic heat-resistant alloy bars, characterized in that, The process involves using the chemical composition of the austenitic heat-resistant alloy as described in claim 1 or 2, and includes the following steps: S1: Vacuum induction melting is carried out. In the later stage of refining, Zr and Ce are added in the form of Si-Zr alloy and Si-Ce alloy respectively. Then, electroslag remelting is carried out to obtain electroslag ingots. S2: Forging the electroslag ingot into a square billet; S3: The billet is hot rolled into a bar, and immediately after rolling, it is cooled by water, followed by water cooling. S4: Cool after solution treatment; S5: The solution-treated bar is cold-drawn and deformed, with a total deformation of 15-19%.
4. The preparation method according to claim 3, characterized in that, In S1, Si-Zr alloy is added when the molten steel temperature is 1420~1450℃, and Si-Ce alloy is added when the molten steel temperature is 1430~1460℃.
5. The preparation method according to claim 4, characterized in that, When adding Si-Zr alloy and Si-Ce alloy, after controlling the vacuum degree of the vacuum chamber to <1Pa, high-purity argon gas is introduced to raise the pressure inside the furnace to 6000~8000Pa, so as to suppress the volatilization of Zr and Ce elements.
6. The preparation method according to claim 3, characterized in that, In S2, the forging opening temperature is 1130~1150℃, and the final forging temperature is 920~940℃.
7. The preparation method according to claim 3, characterized in that, In S3, the hot rolling temperature is 1100~1120℃, and the final rolling temperature is 910~930℃.
8. The preparation method according to claim 3, characterized in that, In S3, the coolant used for water cooling is composed of water, sodium dodecyl sulfate, nano copper oxide powder and nano aluminum oxide powder, wherein the amount of sodium dodecyl sulfate added is 0.20~0.50wt%, and the amount of nano copper oxide powder and nano aluminum oxide powder added is 0.1~0.3wt%.
9. The preparation method according to claim 3, characterized in that, In S5, the cold drawing process involves 2 to 3 consecutive cold drawing deformations.
10. A heat-resistant alloy bar, characterized in that, The heat-resistant alloy rod is prepared by the preparation method described in any one of claims 3-9, and the hardness of the rod is HRC25~HRC35.